The transmembrane channel-like 6 (TMC6) in primary sensory neurons involving thermal sensation via modulating M channels - An, Yating; Hu, Jingyi; Hao, Han; Zhao, Weixin; Zhang, Xiaoxue; Shao, Jicheng; Wang, Caixue; Li, Xinmeng; Liu, Chao; He, Jinsha; Zhao, Yiwen; Zhang, Hailin; et al. (Frontiers in Pharmacology, 2024)
The transmembrane channel-like (TMC) protein family contains eight members, TMC1-TMC8. Among these members, only TMC1 and TMC2 have been intensively studied. They are expressed in cochlear hair cells and are crucial for auditory sensations.TMC6 and TMC8 contribute to epidermodysplasia verruciformis, and predispose individuals to human papilloma virus. However, the impact of TMC on peripheral sensation pain has not been previously investigated. Here, we demonstrated that TMC6 is mainly expressed in small and medium dorsal root ganglion (DRG) neurons and is involved in peripheral heat nociception. Deletion of TMC6 in DRG neurons hyperpolarizes the resting membrane potential and inhibits neuronal excitability.Additionally, the function of the M channel is enhanced in TMC6 deletion DRG neurons owing to the increased quantity of free zinc in neurons. Indeed, heat and mechanical hyperalgesia in chronic pain are alleviated in TMC6 knockout mice, particularly in the case of heat hyperalgesia. This suggests that TMC6 in the small and medium DRG neurons may be a potential target for chronic pain treatment.